Five-to-Fifteen-Parental Perception of Developmental Profile from Age 5 to 8 Years in Children Born Very Preterm - Mäkilä Eeva; Ekblad Mikael O; Rautava Päivi; Lapinleimu Helena; Setänen Sirkku (MDPI, 2025)
Children born very preterm have increased risk of developmental difficulties. We examined the parental perception of developmental profile of children born very preterm at 5 and 8 years by using the parental questionnaire Five-to-Fifteen (FTF) compared to full-term controls. We also studied the correlation between these age points. The study included 168 and 164 children born very preterm (gestational age < 32 weeks and/or birth weight ≤ 1500 g) and 151 and 131 full-term controls. The rate ratios (RR) were adjusted for sex and the father's educational level. At 5 and 8 years, children born very preterm were more likely to have higher scores (more difficulties) compared to controls in motor skills (RR = 2.3, CI 95% = 1.8-3.0 at 5 years and RR = 2.2, CI 95% = 1.7-2.9 at 8 years), executive function (1.7, 1.3-2.2 and 1.5, 1.2-2.0), perception (1.9, 1.4-2.5 and 1.9, 1.5-2.5), language (1.5, 1.1-1.9 and 2.2, 1.7-2.9), and social skills (1.4, 1.1-1.8 and 2.1, 1.6-2.7), and at 8 years in learning (1.9, 1.4-2.6) and memory (1.5, 1.2-2.0). There were moderate-to-strong correlations (r = 0.56-0.76, p < 0.001) in all domains between 5 and 8 years in children born very preterm. Our findings suggest that FTF might help to earlier identify children at the greatest risk of incurring developmental difficulties persisting to school-age.